Sucrose 6F-phosphate phosphorylase: a novel insight in the human gut microbiome. Issue 4 (26th March 2019) - Tauzin, Alexandra S.; Bruel, Laetitia; Laville, Elisabeth; Nicoletti, Cendrine; Navarro, David; Henrissat, Bernard; Perrier, Josette; Potocki-Veronese, Gabrielle; Giardina, Thierry; Lafond, Mickael
Abstract : The human gut microbiome plays an essential role in maintaining human health including in degradation of dietary fibres and carbohydrates further used as nutrients by both the host and the gut bacteria. Previously, we identified a polysaccharide utilization loci (PUL) involved in sucrose and raffinose family oligosaccharide (RFO) metabolism from one of the most common Firmicutes present in individuals, Ruminococcus gnavus E1. One of the enzymes encoded by this PUL was annotated as a putative sucrose phosphate phosphorylase ( Rg SPP). In the present study, we have in-depth characterized the heterologously expressed Rg SPP as sucrose 6 F -phosphate phosphorylase (SPP), expanding our knowledge of the glycoside hydrolase GH13_18 subfamily. Specifically, the enzymatic characterization showed a selective activity on sucrose 6 F -phosphate (S6 F P) acting both in phosphorolysis releasing alpha-d -glucose-1-phosphate (G1P) and alpha-d -fructose-6-phosphate (F6P), and in reverse phosphorolysis from G1P and F6P to S6 F P. Interestingly, such a SPP activity had never been observed in gut bacteria before. In addition, a phylogenetic and synteny analysis showed a clustering and a strictly conserved PUL organization specific to gut bacteria. However, a wide prevalence and abundance study with a human metagenomic library showed a correlation between SPP activity and the geographical origin of the individuals and, thus, most likely linked to diet. Rgspp gene overexpression has been observed in mice fed with a high-fat diet suggesting, as observed for humans, that intestine lipid and carbohydrate microbial metabolisms are intertwined. Finally, based on the genomic environment analysis, in vitro and in vivo studies, results provide new insights into the gut microbiota catabolism of sucrose, RFOs and S6 F P.